Time Analysis of Crude Palm Oil (CPO) Loading and Unloading Activities at the Port of Tana Paser - Reza Fauzi Jaya Sakti; Yosi Pahala; Alhafizh Rizqullah; Shafira Nahdah (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Crude Palm Oil (CPO) is a vegetable oil derived from palm fruit pulp. This oil is naturally reddish in color because it contains high amounts of beta-carotene. Port Business Entity (BUP) is a business entity whose activities are specifically in the field of managing Terminals and other Port Facilities. One of the Port Business Entities in the Tanah Paser area is PT. Jaya Investama Terminal. This terminal utilizes the lease of state-owned goods with one of its business activities being the loading and unloading of Crude Palm Oil. (CPO). In its operations, there are various hindering factors that affect timeliness, resulting in suboptimal loading and unloading activities. This research aims to analyze various inhibiting factors affecting activities at the port. The research was conducted using a quantitative descriptive method approach. Subsequently, the findings were elaborated using a qualitative approach to observe the actual conditions that occurred during the research period. The data collection technique used is the observation technique. The data analysis used includes the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings of the research indicate that the construction of additional storage facilities and the expansion of loading and unloading areas at the port are urgently needed to accommodate larger volumes. And the limited human resources in the CPO loading and unloading process also cause problems in the field, resulting in inefficient loading and unloading activities.